Analysis and Design of Cooperative Control Solutions for Electrical Systems of Laser CNC Machines - Shufeng Shao (Shock and Vibration)
In order to further improve the collaborative control efficiency of the electrical system of the laser CNC machine tool, an electrical system based on the ultrafast laser CNC machine tool is proposed. The design of the collaborative control scheme is discussed from three aspects: the overall control scheme design, hardware structure design, and control software implementation of the electrical system of the laser numerical control machine tool. The experimental results show that the length of the metal sheet processed by the electrical system of the laser CNC machine tool is 5.3 cm and the width is about 3.6 cm, and the actual processing aperture size will also change according to the set number of variable radius turns, and more precise processing can be enabled in the online test. The research results show that this electrical collaborative control system scheme has strong practicability and feasibility. With the help of system upgrades and optimization, the efficient integration of laser processing technology and numerical control technology can be better achieved. It should be noted that the machining process of the machine tool is also required to make in-depth improvements, which can maximize the operating efficiency and machining accuracy of the electrical system of the CNC machine tool. The laser CNC machine tool researched and developed in this paper verifies the rationality and feasibility of the collaborative control scheme through practical experiments, which can meet the processing requirements and realize the integration of laser processing technology and numerical control technology. High machining efficiency and machining accuracy.